PENGARUH TATA KELOLA PERUSAHAAN DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Meisya, Meisya; Rinjani, Rinjani (E-Jurnal Akuntansi TSM, 2023)
This study aims to provide empirical evidence that corporate governance consisting of institutional ownership, independent commissioners, board of directors’ size, and company size, also leverage, return on assets, and sales growth has an influence towards earnings management. The population that is used in this research are non-cyclicals and cyclicals companies listed in the Indonesia Stock Exchange from 2020 to 2022. The sampling method used purposive sampling, with a total sample of 64 companies or 192 data that met criteria. This research uses multiple regression method. The results of this research indicate that all independent variables, namely institutional ownership, independent commissioners, board of directors’ size, company size, leverage, return on assets, free cash flow and sales growth have no influence on earnings management.